Sengketa Hak Cipta Lagu Kasus Lesti Kejora dan Yoni Dores dalam Sorotan Publik - Faizin, Faizin; Ekaningsih, Lailasari; Ahmad, Ridho Sa’dillah; Fatmawati, Anna; Askamilati, Putri Risky; Saputri, Nova Ana (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2025)
The copyright dispute between Lesti Kejora and Yoni Dores has drawn public attention due to its complexity and the broader challenges of intellectual property protection in the digital era. This study aims to examine the legal implications of alleged copyright infringement, inefficiencies in royalty management systems, and the influence of public response on the dispute resolution process. The research employs a normative juridical method with a qualitative approach by analyzing statutory regulations, case studies, and legal literature. The findings indicate that Lesti Kejora’s commercial use of a song owned by Yoni Dores without proper authorization may constitute a violation of Article 9 paragraph (1) and Article 113 paragraph (3) of the Indonesian Copyright Law. Key issues include the lack of effectiveness and transparency in the performance of Collective Management Organizations (LMK) and the National Collective Management Organization (LMKN), exacerbated by the absence of a national digital system. Additionally, there is widespread misunderstanding among creative industry players regarding licensing requirements. Compared to countries with integrated, technology-based copyright systems and strong legal culture, Indonesia still lags significantly. The Lesti Kejora Yoni Dores case highlights the urgent need for comprehensive reform in Indonesia's copyright protection system.